Identification of salt tolerance‐improving quantitative trait loci alleles from a salt‐susceptible rice breeding line by introgression breeding - Qiu, Xianjin; Yuan, Zhihua; Liu, Huan; Xiang, Xiaojiao; Yang, Longwei; He, Wenjing; Du, Bin; Ye, Guoyou; Xu, Jianlong; Xing, Danying (Wiley, 2015)
To improve salt tolerance of two elite rice varieties, Ce258 and Zhongguangxiang1 (ZGX1), two sets of introgression lines (ILs) each comprising 200 BC1F10lines derived from a common donor, IR75862, and two recipient parents, Ce258 and ZGX1, were used for mapping of QTLs for four salt tolerance‐related traits at the seedling stage. Although the three parents were susceptible to salt, the two IL populations showed transgressive segregations for salt tolerance with 12 and 8 salt tolerance ILs in the Ce258‐ILs and ZGX1‐ILs. Eighteen main‐effect QTLs were identified for the four traits in the two IL populations, and the IR75862 alleles at most loci showed increased and decreased salt tolerance in the ZGX1 and Ce258 backgrounds, suggesting overwhelming genetic background effects on QTL detection for salt tolerance. TheqDSS11simultaneously detected in the two backgrounds was validated in a F2population derived from a salt tolerance line and ZGX1. Our results indicated that salt tolerance‐enhancing allele could be identified in the elite susceptible breeding lines and that introgression of the favourable alleles could facilitate the development of superior lines with greater salt tolerance levels.